Geoecological analysis of short-term trends changes in the structure of NPP "Slobozhanskiy" territory based on satellite imagery PlanetScope - Бодня, О. В.; Овчаренко, А. Ю.; Черваньов, І. Г. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. The article analyses changes in landscape structure of the territory of National Nature Park “Slobozhanskiy” using satellite imagery for obtaining the actual material of plant communities, work in the field examining facies’ contours on the basis of GIS-technology. The research comprises the territory of unique wetlands.The purpose of the article is to show the results of a single physical-geographical process manifestations on the objects of the protected area through changes observation (monitoring) that can be fixed by decoding remote sensing data.Methods. The main methods of research are the analysis of remote sensing data and control field landscape surveys, including the innovative online use of portable mobile devices (smartphones) to trace contours and create databases using mobile GIS.Results. The authors reveal the possibility of using satellite imagery data for landscape monitoring. The study presented the choice of satellite images, methods of their processing. The paper highlights the possibility to use ArcGis tools for decryptting the data of PlanetScope imagery and further overlay analysis based on the data of topography, geological structure, soil cover and vegetation. The authors substantiate the need for large-scale mapping of the study area.Scientific novelty and practical significance is in the choice of classification and postclassification methods, processing thematic imageries of vegetation. For the study area, the best results were obtained using satellite imageries PlanetScope with a spatial resolution of 3 meters. These processes affect changes in the plant structure, and,consequently, in landscape structure in general. In the study we have found that there are not only seasonal fluctuations but also a gradual decrease in the water surface and swamping. Landscape monitoring using GIS technologies allows you to quickly update information and predict future changes based on the collected data.